“Why do you want to be a doctor?” A mixed-methods cross-sectional study of motivations among first-year medical students at a medical school in Mauritius - Jatain, Navita; Sharma, Rudraksh; Banerjee, Shradha; Dodia, Krishna; Deshwali, Sanjay Kumar; Roy, Bedanta; Banerjee, Indrajit (Journal of Biomedical Sciences, 2025)
Background: The primary objective of the study was to identify the motivational factors influencing the choice of medicine among first-year medical students to become doctors in Mauritius. Material and methods: A mixed-methods cross-sectional study was conducted at Sir Seewoosagur Ramgoolam Medical College, Mauritius, in November 2025. Results: Of the 140 medical students enrolled in the first-year medical course, 110 students participated in the study, yielding an overall response rate of 78.57% (50 female, 45.45%; 60 male, 54.54%). Most were Mauritian (n=63, 57.2%), followed by Indian (n=35, 31.8%) and South African (n=11, 10.0%) students. Altruism was the most commonly reported motivation for choosing medicine. Specialty preference differed significantly by gender (χ²=15.73, p=0.008): females more often preferred Paediatrics and Obstetrics and Gynaecology, whereas males more often preferred Surgery. Students with a family member in healthcare were more likely to report prior exposure (χ²=4.97, p=0.026), but family attitudes were not significantly associated with perceived preparedness (χ²=10.28, p=0.246). An inductive thematic analysis was conducted for the qualitative domain, and two themes were generated from various codes/nodes: namely Intrinsic factors and Extrinsic factors. Each theme had different categories. Conclusion: Medical students’ choice to pursue medicine was primarily driven by intrinsic motivations, particularly altruism, compassion, and a sense of calling. While extrinsic factors such as career stability, financial security, and social status also influence decision-making, they function as a reinforcing influence rather than primary driving forces.